A4 A FRAMEWORK TO STUDY INFLAMMATORY BOWEL DISEASE AMONG INDIGENOUS PEOPLES AND PRELIMINARY RESULTS FROM SASKATCHEWAN, CANADA. (26th February 2020) - Peña-Sánchez, J; Jennings, D; Andkhoie, M; Brass, C; Bukassa-Kazadi, G; Fowler, S; Johnson-Jennings, M; Marques Santos, J D; Osei, J A; Porter, L; Porter, R; Quintin, C; et al.
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic condition with significant life-threatening disease-related complications and reductions in quality of life if left untreated. Despite available research about IBD in the general population, there is limited-to-no evidence about IBD among Indigenous peoples in Canada and around the world. Aims: We aimed to define a collaborative framework, estimate the prevalence and incidence rates of IBD among First Nations in Saskatchewan, Canada, and explore perceptions of IBD among Indigenous peoples in the province. Methods: This study began when Indigenous patients shared their health experiences with IBD with research team members. An interdisciplinary research team was formed including Indigenous patient and family advocates (IPFAs, Indigenous patients living with IBD and parents of an Indigenous person with IBD), an IBD gastroenterologist, knowledge users, and Indigenous and non-Indigenous researchers. Our research team committed to raise awareness of IBD among Indigenous peoples within Indigenous communities and among health care providers and to advocate for better healthcare and well-being by providing evidence of IBD among Indigenous peoples living with IBD in Saskatchewan. We defined a mixed methodology. The first phase of the study used Saskatchewan administrative health data to estimate the prevalence and incidence rates with 95% confidence intervals (95%CI) of IBD among First Nations. The second phase of the study will use a photovoice methodology to gather "the voices" of Indigenous peoples with IBD, encouraging self-interpretation of pictures, engaging their communities, and empowering them with the study findings. Results: The IPFAs play a critical role in the project by sharing their experiences and defining the directions of the project, as well as defining our research framework (Figure 1). Preliminary results show that the prevalence of IBD among First Nations in Saskatchewan increased from 66 (95%CI 65–68) per 100, 000 population in 1999 to 148 (95%CI 145–151) per 100, 000 people in 2015. In contrast, the incidence rates appear to be stable over time, 11/100, 000 (95%CI 4–24) in 1999 and 11/100, 000 (95%CI 5–20) in 2015. We started recruiting participants for the photovoice study in September 2019. Conclusions: This ground-breaking patient-driven study is the first stage to improve health among Indigenous peoples living with IBD in Saskatchewan. This project will generate community-engaged knowledge and expertise to inform the development of an Indigenous IBD framework that could promote better and knowledge-based healthcare for Indigenous peoples with IBD in Canada and worldwide. Funding Agencies: CIHRSaskatchewan Health Research Foundation (SHRF) and Saskatchewan Centre for Patient-Oriented Research (SCPOR)